Pengaruh Kepemimpinan Transaksional Terhadap Prestasi Kerja Pegawai di Wilayah Kerja Kecamatan Karang Penang Kabupaten Sampang yang Dimediasi Oleh Semangat Kerja - Sri Mulyani; Chamariyah Chamariyah; Turmuri Turmuri (Universitas 45 Surabaya, 2024)
This type of research is explanatory research, the approach used is a quantitative approach, the research sample is 42 people. The analysis tool uses Smart PLS (Partial Least Square). Research objectives: 1) To prove and analyze whether transactional leadership has a direct influence on the work performance of employees at the Karang Penang District Office, Sampang Regency. 2) To prove and analyze whether transactional leadership has a direct influence on the work spirit of the Karang Penang District Office, Sampang Regency. 3). To prove and analyze whether work enthusiasm has a direct influence on the work performance of employees at the Karang Penang District Office, Sampang Regency 4) To prove and analyze whether transactional leadership has an indirect influence on employee work performance which is mediated by work morale at the Karang Penang District Office, Sampang Regency. The research results show that: 1) Transactional leadership does not have a significant positive effect on employee work performance as evidenced by the original sample value of 0.280 and p-values ​​of 0.058. 2) Transactional leadership has a significant positive effect on work morale as evidenced by the original sample value of 0.377 and p-values ​​of 0.015. 3) Work morale has a significant positive effect on employee work performance as evidenced by the original sample value of 0.557 and p-values ​​of 0.000. 4) Transactional leadership has a significant positive indirect effect on employee work performance and work morale as evidenced by the original sample value of 0.210 and p-values ​​of 0.022.